Microbial death in the Andes: necromass declines despite growth and carbon-use-efficiency increases with decadal soil warming - Nottingham, A.T.; Karhu, K.; Salinas Revilla, N.; Schnecker, J.; Sietiö, O.-M.; Martin Vivanco, A.K.; Wanek, W.; Meir, P. (Elsevier, 2026)
The growth and death of soil microbes are important drivers of soil carbon formation. A warming climate is predicted to affect both the production of microbial biomass and the stability of microbial residues (necromass) held in soils. However, we have very little information on how warming in tropical soils will affect these processes, and on the effect of temperature on microbial production and turnover over different time-scales. To address this, we studied temperature effects on microbial-mediated C cycling across two different time-scales, using a 20 ⁰C mean annual temperature gradient in the Peruvian Andes (long-term effects) and decadal experimental-warming via soil translocation (11-years of temperature effects). At long-term timescales, a legacy of warmer temperatures decreased microbial carbon use efficiency (CUE), microbial biomass C, and decreased fungal and bacterial necromass concentration in soils. At decadal timescales, experimental warming increased CUE, microbial production and microbial biomass concentration (likely the result of concomitant changes in substrate availability). However, this did not translate into increased microbial necromass concentration, which generally declined with warming across all temporal scales. Together, we show that warmer temperatures over decadal (11-year) timescales affect soil microbial processes to potentially increase their C input to soil (increased CUE, microbial production, and biomass) but we find no evidence that this C became stabilized as the necromass C pool decreased. Our results indicate that warming can alter microbial community metabolism to potentially increase necromass C inputs to soil, although we find no evidence to show that this offset overall soil C loss with warming.
Keywords: Soil carbon; Global warming; Biomass (ecology); Microbial population biology; Climate change; Carbon cycle; Soil water; Global change; https://purl.org/pe-repo/ocde/ford#1.06.13